Constructing meaning and its intellectual representations in films of racial discrimination (Journal of the College of Basic Education, 2024)
Since ancient times, the means and tools of communication have carried contents and intellectual forms that carry within them messages and goals to achieve a goal and towards a target audience by striving to achieve a retrospective effect on the target audience for the purpose of delivering a systematic message with one-way codified opinions and ideas that include multiple axes from the walks of life and people to imitate the audience and touch data many of its neighbourhoods And what touches his life through multiple expressive connotations and in various media, including cinema and television, and employing them to deliver contents with specific goals because of its wide spread and transcending the boundaries of time and space. Easily accessible to everyone, it is considered an entertainment, educational, social and communication tool between the peoples of the world, individuals and societies. And it became in contact with the life of the individual, synchronized with him, and influenced him through cultural, historical, political, and various other topics, which contribute to bringing about change and a psychological impact by changing views and attitudes by considering cinema as a communicative means for reviewing ideas and transferring them between societies, and among the uses of the audio-visual medium through artistic treatment emerged directing A very important topic that has emerged through multiple artistic productions in cinema throughout history that simulate the issue of extremism Racism through cinematic films and through establishing the concept of practicing exclusion, retaliation and abuse towards race, color, religion, gender, minorities, cultures, rituals and customs of peoples. As the research aims to study the subject in its aspects, and from this point of view, the researcher formulated the research problem to launch his study by asking the following question: What are the technical uses and treatments to build meaning and its intellectual variables in films whose contents bear the characteristics of racial discrimination, and since it aims to reveal the construction of meaning and its intellectual variables in films of racial discrimination The descriptive approach (content analysis) was adopted as it is more appropriate to achieve the goals and reach the desired results,